2003
DOI: 10.1007/s00248-002-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Microbial Communities in Sphagnum Peatlands and Effect of Atmospheric Carbon Dioxide Enrichment

Abstract: Little is known about the structure of microbial communities in Sphagnum peatlands, and the potential effects of the increasing atmospheric CO2 concentration on these communities are not known. We analyzed the structure of microbial communities in five Sphagnum-dominated peatlands across Europe and their response to CO2 enrichment using miniFACE systems. After three growing seasons, Sphagnum samples were analyzed for heterotrophic bacteria, cyanobacteria, microalgae, heterotrophic flagellates, ciliates, testat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…For example, glucose is known to attract motile hormogonia of the nitrogen-fi xing cyanobacterium Nostoc , which subsequently takes up symbiotic residence within the tissues of various land plants ( Nilsson et al, 2006 ). The N 2 -fi xing cyanobacteria Nostoc , Anabaena , Tolypothrix , and Stigonema are common peat moss associates ( Basilier, 1980 ;Hingley, 1993 ;Mitchell et al, 2003 ), andBasilier (1980) demonstrated that nitrogen compounds produced and exuded by N. muscorum Allison are absorbed by Sphagnum and transported upward in the stem. Ecological theory predicts that plants of infertile sites should use exudates to foster the growth of microbes that provide scarce nutrients ( Paterson et al, 2006 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, glucose is known to attract motile hormogonia of the nitrogen-fi xing cyanobacterium Nostoc , which subsequently takes up symbiotic residence within the tissues of various land plants ( Nilsson et al, 2006 ). The N 2 -fi xing cyanobacteria Nostoc , Anabaena , Tolypothrix , and Stigonema are common peat moss associates ( Basilier, 1980 ;Hingley, 1993 ;Mitchell et al, 2003 ), andBasilier (1980) demonstrated that nitrogen compounds produced and exuded by N. muscorum Allison are absorbed by Sphagnum and transported upward in the stem. Ecological theory predicts that plants of infertile sites should use exudates to foster the growth of microbes that provide scarce nutrients ( Paterson et al, 2006 ).…”
Section: Resultsmentioning
confidence: 98%
“…A second goal was to obtain insight into the ecological roles of mixotrophy in bryophytes and charophyceans. To accomplish this, we quantitatively analyzed the growth responses to exogenous sugar of two representatives of Zygnematales, a relatively early-diverging charophycean lineage recognized for high diversity and abundance in peatlands and associated humic lakes (Graham and Wilcox, 2000;Mitchell et al, 2003), and Sphagnum compactum Lam. & DC, a representative emergent peat moss species whose compact structure facilitates physiological study in the laboratory.…”
Section: Carbon-limitation Experimentsmentioning
confidence: 99%
“…In peatbogs, testate amoebae represent an ideal model group for microbial food web studies owing to their abundance, diversity and ubiquity (Jassey et al, ). Due to the clear predominance of testate amoebae in peatbogs, they are recognised as having the most important role in matter and energy flow (Mitchell et al, ; Nguyen‐Viet et al, ). These protozoans are significant consumers of bacteria, flagellates and algae, and participate in mineralisation of organic matter and circulation of biogenic compounds (Gilbert et al, ; Wilkinson and Mitchell, ; Mieczan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the physiochemical and botanical properties of the underlying peat have been shown to affect strongly (i) the growth of Sphagnum mosses (Grosvernier, Matthey & Buttler 1997; Buttler, Grosvernier & Matthey 1998) and (ii) gas fluxes to the atmosphere (Buttler, Dinel & Lévesque 1994; Charman, Aravena & Warner 1994) while microbial communities have been shown to respond to ecological gradients as well as ecosystem perturbations, such as nitrogen input and elevated atmospheric CO 2 concentrations (Gilbert et al . 1998a,b; Mitchell et al . 2003).…”
Section: Introductionmentioning
confidence: 99%